Opportunities for improving water and land management in Sub-Saharan Africa: research priorities of IWMI's Africa Program - Bahri, Akissa; Awulachew, Seleshi Bekele; Sally, Hilmy; Ul-Hassan, Mehmood (2007)
Africa, particularly Sub-Saharan Africa (SSA) is faced with deep rooted poverty, malnutrition and inadequate food production. Key factors that aggravate these problems include high population growth, low agricultural productivity, high natural and man-made tragedies such as climatic variability and change, conflicts and war. About 70% of SSA's economy is dependent on agriculture and the majority of the population is engaged in agriculture. Given the low labor, land and water productivities in most parts of SSA, production growth in SSA has come primarily from extending agricultural land and not on intensifying agriculture. This also has substantial implication on the environment. There is however tremendous scope and opportunity to reverse these trends, improve livelihoods and create wealth. It is against this background that the programs and contributions of the International Water Management Institute (IWMI) towards improved water and land management in Africa for agricultural and other developments are presented in this paper. IWMI's roles in terms of understanding the challenges and the importance of water and land management are emphasized. The functional arrangements of IWMI's sub- regional offices and their respective research priorities, the current key research, capacity building and knowledge management activities of IWMI in Africa, and its research partnerships are discussed.